FREQUENCY OF HEPATITIS-B CARRIERS AMONG CHILDREN IN DERA GHAZI KHAN URBAN SLUMS - Muhammad Saleem Channer; Zahid Masood; Ghulam Qasim Khan Khichi (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: To ﬁnd out the seroprevalence of Hepatitis “B” carriers among children in Dera Ghazi Khan urban slums. DESIGN: An observational descriptive cross-sectional study. SETTING: Dera Ghazi Khan urban slums and Paediatric Medicine Unit in Teaching Hospital Dera Ghazi Khan. SUBJECTS: Five hundred ﬁfty children admitted to Paediatric Unit in Teaching Hospital Dera Ghazi Khan and those in urban slums of Dera Ghazi Khan City. MAIN OUTCOME MEASURES: Seroprevalence of Hepatitis “B” carriers. RESULTS: Mean age of children in our study was 7.5 years. Males were 54%. The number of children detected as carriers of Hepatitis B was 16 (2.9%). Out of 16 carriers, 7 had successfully completed their EPI schedule, 4 received incomplete vaccination while 5 carriers did not receive any EPI schedule vaccination. Just one seropositive case gave past history of jaundice in his early neonatal period for which he got exchange transfusion. None of the carriers got tattooing nor shared piercing of nose or ears by a common (contaminated) needle. There were no signs suggestive of chronic liver disease in any carrier. CONCLUSION: Overall seroprevalence of Hepatitis-B carriers in Bahawalpur is 2.9%. There is a large cohort of seronegative children. They need to be protected against HBV infection through active immunization.